Implementasi Pelatihan Sadar Wisata Bahari Berbasis Karakter di Pantai Cemara Kabupaten Bireuen - Novalita, Rahmi; Sumanti, Sumanti; Carvina, Mona (Aceh Journal of Community Engagement (AJCE), 2024)
Bireuen Regency has many tourist attractions that are worth visiting by the public. The tourist attractions in Bireuen are very good and worth visiting by tourists, but tourists and visitors are reluctant to visit several tourist attractions in Bireuen for several reasons. One aspect of tourism development is tourism awareness. Tourism awareness is community participation in creating tourist areas in accordance with the seven charms of tourist attractions. Lecturers and students of Almuslim University tried to carry out community service activities at the Cemara Beach tourist attraction in the form of community service activities, namely "Implementation of Tourism Awareness Education for Character-Based Marine Tourism Visitors". Training was also provided to provide an understanding of tourism awareness to the community and visitors at Cemara Beach. As a result, the community can increase tourism awareness and this community service activity can improve the ability of tourist attraction managers to manage the tourist attractions.